PERAN E-WALLET DAN PROMOSI DALAM KEPUTUSAN PEMBELIAN MICROTRANSACTIONS: STUDI PADA KOMUNITAS UNSEC - Leonard Yvanno; Khresna Bayu Sangka; Salman Alfarisy Totalia (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study addresses the issue of how the use of e-wallets and sales promotions influence students' purchase decisions for microtransactions and examines the role of digital financial literacy in moderating these effects. The purpose of this research is to assess the impact of e-wallet usage and promotional activities on purchase decisions, while determining whether digital financial literacy strengthens or weakens these influences. The population comprises 485 students who are members of Universitas Sebelas Maret E-sport Community (UNSEC), with a sample of 219 students selected through purposive sampling. Data was collected via an online questionnaire and analyzed using descriptive statistics, multiple linear regression, moderated regression analysis (MRA), t-tests, and coefficient of determination. Validity testing employed Pearson Product Moment, and reliability was assessed using Cronbach’s Alpha. Findings indicate that e-wallet usage and sales promotions have a significant positive effect on purchase decisions, with a significance value of 0.000. However, digital financial literacy weakens the influence of both variables, as shown by a decrease in the R square value from 45.7% to 32.8% after moderation. In conclusion, while e-wallet usage and sales promotions play essential roles in driving microtransaction purchase decisions, digital financial literacy reduces their impact, highlighting the importance of digital financial understanding in shaping students’ purchase decisions.